Tren Penelitian Bibliometric pada Jurnal Media Pustakawan Tahun 2015-2022 - Thamrin Hasan (Perpustakaan Nasional, 2023)
The study was conducted to determine bibliometric research trends in Media Pustakawan journals accredited at SINTA. The purpose of the study is to provide an overview of the development of scientific publications related to content analysis of articles published in Media Pustakawan journals from 2015-2022. The data is taken from media librarians who have been accredited at SINTA. In total, there are 211 scientific research articles published. Next, the bibliometric review articles from these journals were collected. Articles published before January 2023. Of the 211 articles collected, there are 27 articles that examine bibliometrics. The results of the study showed that the types of quantitative research found 24 (88.89%) articles, the types of research articles found 26 (96.30%), research objects sourced from 22 journals (81.48%), the data collection instrument used Microsoft Excel worksheet found 16 (59.26%) articles, the bibliometric study group in descriptive form found 14 (51.85%) articles, and data analysis using percentages found 19 (70.37%) articles. Furthermore, the results of the authorship aspect based on the type of researcher found 15 (55.56%) collaborated, 21 (53.85%) research was conducted by women, 18 research institutions (66.67%) were non-university researchers, and 25 research areas (92.59%) came from the island of Java. The conclusion of this study is that the research trend of Media Pustakawan journals has increased and librarianship studies are increasingly in demand as a research area in Indonesia. Then, the topic of bibliometric research is of sufficient interest to researchers.